Caracterização do grupo Edessa rufomarginata e descrição de sete novas espécies (Heteroptera, Pentatomidae, Edessinae) - SILVA, Eduardo José Ely e (2013)
The Edessa group rufomarginata is proposed to include E. rufomarginata (De Geer, 1773), E. marginalis (Dallas, 1851), E. albomarginata (Stål, 1855), E. abdominalis Erichson, 1848, E. corallipes Erichson, 1848, E. aulacosterna Stål, 1872, E. ovalis Stål, 1872, and E. nigropunctata Berg, 1884. Seven new species are described in this group, six from Brazil and one from Argentina: E. brasiliensis sp. nov., E. castaneolineata sp. nov., E. cerradensis sp. nov., E. chapadensis sp. nov., E. luteovenulata sp. nov., E. rufodorsata sp. nov. (Argentina) and E. virididorsata sp. nov. These species are known from Venezuela, Suriname, Guyana, Brazil, Paraguay and Argentina.